Diagnosis and Management of Obstructive Sleep Apnea in the Perioperative Setting - Lyons, Patrick G.; Mokhlesi, Babak (Seminars in Respiratory and Critical Care Medicine, 2014)
Obstructive sleep apnea (OSA) is a chronic prevalent condition which may be under-recognized in surgical populations. Patients with OSA may be at increased perioperative risk, in part due to the effects sedatives and anesthetics have on upper airway tone and respiratory drive. A growing amount of data suggests that OSA patients have increased odds for adverse postoperative outcomes including intensive care unit transfer, respiratory failure, arrhythmias, and cardiac ischemia. Several screening tools have been developed to identify patients at risk for OSA preoperatively, but it remains to be seen whether routine implementation of these tools improves outcomes. In this review, we discuss the perioperative complications of OSA, the tools with which physicians can screen surgical patients, and the perioperative management of these patients.
Keywords: sleep-disordered breathing; obstructive sleep apnea; perioperative; postoperative; complications; continuous positive airway pressure